Tertiary carbonate side chains: easily tunable thermo-labile breaking points for controlling the solubility of conjugated polymers - Kuhn, Marius; Ludwig, Jens; Marszalek, Tomasz; Adermann, Torben; Pisula, Wojciech; Müllen, Klaus; Colsmann, Alexander; Hamburger, Manuel (Chemistry of materials, 2015)
We present a new class of solubilizing groups for conjugated polymers that enable solution processing of multilayer devices. Conjugated polymers in organic devices are sometimes difficult to process, because of their limited solubility. Well-soluble polymers decorated with alkyl side chains, however, introduce new challenges for thin-film deposition. Using the same solvent for multiple layers can dissolve the already applied layers. In this work, we introduce a new class of thermo-labile groups, which reduce the solubility of conjugated polymers after thermal treatment. Following a very modular approach, we can tune the temperature of the thermo-cleavage between 140 °C and 200 °C. This enables the fabrication of organic solar cells and field-effect transistors (FETs) with robust, solvent-resistant active layers.